2017
DOI: 10.1177/0898264317703559
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation and Medicare Spending: Among Older Adults, Objective Isolation Increases Expenditures While Loneliness Does Not

Abstract: Objectives Evaluate objective isolation and loneliness’ impact on Medicare spending and outcomes. Methods We linked Health and Retirement Study data to Medicare claims to analyze objective isolation (scaled composite of social contacts and network) and loneliness (positive response to 3-item loneliness scale) as predictors of subsequent Medicare spending. In multivariable regression adjusting for health and demographics, we determined marginal differences in Medicare expenditures. Secondary outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 52 publications
(90 reference statements)
3
78
2
1
Order By: Relevance
“…Our study also found that overall nursing home utilization (as indicated by number of nursing home nights) is similar for lonely and nonlonely individuals, which is supported by others using Medicare claims data . However, we also observed that lonely older adults have higher odds of dying in a nursing home, a troubling finding because it may further isolate lonely people from their communities and support systems, and worsen quality of life near death.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study also found that overall nursing home utilization (as indicated by number of nursing home nights) is similar for lonely and nonlonely individuals, which is supported by others using Medicare claims data . However, we also observed that lonely older adults have higher odds of dying in a nursing home, a troubling finding because it may further isolate lonely people from their communities and support systems, and worsen quality of life near death.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are consistent with other studies that showed no difference in hospitalizations among lonely vs nonlonely older adults. A study by Shaw and colleagues found that lonely individuals have lower Medicare expenditures compared with nonlonely individuals, some of which may be related to lower inpatient expenditures after adjusting for socioeconomic and health status . However, this study did not specifically evaluate changes in healthcare expenditures or utilization near death.…”
Section: Discussionmentioning
confidence: 90%
“…88 Furthermore, reduced social participation is a risk factor for depression, cognitive decline, increased health-care costs, and overall mortality. [6][7][8][9] Our review reveals how PD impairs general social functioning and the ability to fulfill specific roles. A number of symptoms associated with reduced social functioning can be targeted in order to improve function and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…4 Changes in social role functioning are particularly troublesome because satisfaction with social role performance is related to overall happiness and quality of life (QoL). [6][7][8][9] QoL has become a frequent outcome of interest in clinical trials and is one of the most important factors for determining clinical care for people with chronic diseases. [6][7][8][9] QoL has become a frequent outcome of interest in clinical trials and is one of the most important factors for determining clinical care for people with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation